Bahasa dan Ekspresi Politik (Studi Critical Discourse Analysis terhadap Akun Instagram Satir @Nurhadi_Aldo) - Nunik Hariyanti; Senja Yustitia (Universitas Muhammadiyah Ponorogo, 2020)
Reforms bring consequences of freedom in political, contending, and media freedom. In the freedom of media, the presence of new media is dynamic in the process of delivering messages and opinions, especially in the realm of democracy. Black issues, polarisation supporters until identity politics also coloring the Indonesian elections in Indonesia in 2019, until finally, the figure @nurhadi_aldo emerged as the presidential candidate version of the Cyber Society. This research discusses text analysis in a discourse, according to Fairclough, the presence of text is a representation of the understanding of the creator, and this is open to interpretation. The purpose of this study describes the use of sexuality and satire language as a form of political expression in Indonesia, especially those that appear on the Nurhadi - Aldo Instagram account (@nurhadi_aldo). There are three stages to analyzing discourse based on Norman Fairclough's critical discourse analysis theory, namely representation, relation, and identity. The research results show that the language of sexuality and satire used by @nurhadi_aldo is a form of honesty expression to criticize the loss of the essence of an election contestation in Indonesia. Then found bizarre disclosure techniques, hyperbola, contrast, and unexpected techniques of logic use as an attempt to criticize the political phenomenon with @nurhadi_aldo.